MATLAB programming for biomedical engineers and scientists - King, Andrew P. (Academic Press is an imprint of Elsevier, 2017)
MATLAB Programming for Biomedical Engineers and Scientists provides an easy-to-learn introduction to the fundamentals of computer programming in MATLAB. This book explains the principles of good programming practice, while demonstrating how to write efficient and robust code that analyzes and visualizes biomedical data. Aimed at the biomedical engineer, biomedical scientist, and medical researcher with little or no computer programming experience, it is an excellent resource for learning the principles and practice of computer programming using MATLAB. This book enables the reader to: Analyze problems and apply structured design methods to produce elegant, efficient and well-structuredïÅ½program designsImplement a structured program design in MATLAB, making good use of incremental development approachesWrite code that makes good use of MATLAB programming features, including control structures, functions and advanced data typesWrite MATLAB code to read in medical data from files and write data to filesWrite MATLAB code that is efficient and robust to errors in input dataWrite MATLAB code to analyze and visualize medical data, including imaging data.
Keywords: MATLAB.; MATLAB; Numerical analysis -- Data processing.; elektronické knihy; electronic books